Preparation method of amino-functionalized FeOOH nanosheet for treating uranium-containing wastewater
By introducing amino functional groups on the surface of FeOOH, amino functionalized FeOOH nanosheets were prepared, which solved the problem of insufficient adsorption performance of FeOOH on uranium and achieved efficient adsorption and selectivity improvement of uranium.
Patent Information
- Application Number
- CN202411870341.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-11
AI Technical Summary
The hydrophobic properties and poor selectivity of FeOOH limit its adsorption properties to uranium.
Aminofunctionalized FeOOH nanosheets were prepared by introducing amino functional groups on the FeOOH surface. The process includes adding CTAB and iron precursor to the reaction vessel, adjusting the pH value, and stirring under the protection of an inert gas, followed by adding dropwise sodium borohydride solution, and continuing to stir to form the first solution. Then, α-FeOOH was mixed with toluene, dispersed evenly by ultrasound, and the pH was adjusted using an acid regulator, followed by heating and slowly dropping APTES, and amino modification was performed, and amino functionalized FeOOH nanosheets were obtained by vacuum drying.
The adsorption performance of FeOOH on uranium is significantly improved, its selectivity and hydrophilicity are improved, so that it can exhibit excellent adsorption effect when treating uranium-containing wastewater.
Smart Images

Figure CN119406368A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorption materials, and in particular to a method for preparing amino-functionalized FeOOH nanosheets for treating uranium-containing wastewater. Background Art
[0002] In recent years, with the aggravation of environmental pollution and energy shortage, there is an urgent need to develop clean energy. Nuclear energy has attracted widespread attention as a green, reliable and safe energy source. However, the nuclear fuel cycle inevitably produces a large amount of radioactive waste, which poses a serious threat to human health and environmental safety. Among all radioactive substances, uranium (U) is one of the most abundant and dangerous radionuclides in nuclear waste. Therefore, the rational disposal of uranium-containing waste is of great significance to the ecosystem and human health. To date, a variety of technologies have been used to purify radioactive water caused by uranium contamination, including ion exchange, adsorption, membrane separation, solvent extraction, chemical precipitation, photocatalysis, evaporation concentration, biosorption, etc. Among these technologies, the adsorption method has been widely used to treat uranium in aqueous solution due to its advantages such as simplicity, rapidity, wide applicability, high cost-effectiveness and no secondary pollution. Xia et al. synthesized potassium tripolyphosphate cross-linked chitosan (CTPP) and monochloroacetic acid-potassium tripolyphosphate cross-linked chitosan (MCTPP) for UO2 in acidic radioactive wastewater. 2+ The removal results showed that the maximum adsorption capacity of MCTPP was as high as 1487.72 mg / g (Journal of Hazardous Materials 431 (2022) 128461).
[0003] The key to the adsorption method is to develop an adsorbent material that can adapt to the marine environment, has selectivity, low operating costs and excellent stability. At present, the adsorbent materials used in the adsorption method can be divided into four categories: inorganic, organic, inorganic-organic composite, and biological. Among them, the inorganic-organic composite adsorbent has both good adsorption performance and good stability. As an inorganic-organic composite adsorbent, iron oxyhydroxide (FeOOH) has a high specific surface area and excellent chemical properties, so it has strong adsorption capacity and a basis for chemical modification. It is widely used in the adsorption of metal ions and the degradation of organic matter in water. However, the hydrophobic properties and poor selectivity of FeOOH severely limit its adsorption of uranium. The introduction of amino functional groups on the surface of FeOOH can significantly improve the hydrophilicity of the material and its selectivity for uranium, thereby greatly improving the adsorption performance of FeOOH for uranium. At present, the preparation methods of FeOOH usually include hydrolysis, hydrothermal, coprecipitation and ferrous oxidation. During the synthesis process, many factors will significantly affect the morphology, size and crystal structure of the final product, and thus affect its adsorption capacity for uranium, such as the type of iron salt used, the type of precipitant selected, the temperature during synthesis, the duration of the reaction, the pH value of the solution, the concentration of the reactants, the type of surfactant and its ratio, etc. Therefore, it is of great significance to control the conditions to prepare FeOOH-based composite materials with high specific surface area, specific functional groups and excellent adsorption performance. Summary of the invention
[0004] The present invention aims to provide a method for preparing amino-functionalized FeOOH nanosheets for treating uranium-containing wastewater, which solves the problem that the hydrophobic properties and poor selectivity of FeOOH severely limit its adsorption of uranium.
[0005] In order to achieve the above object, the technical scheme of the present invention is as follows: A method for preparing amino-functionalized FeOOH nanosheets for treating uranium-containing wastewater comprises the following steps: S1, adding CTAB and iron precursor into a reaction container, and adding 30-60 mL of deionized water thereto, then adjusting the pH of the solution to acidic, and then stirring for 30-60 minutes under the protection of an inert gas to obtain a first solution; S2, dissolving a certain amount of sodium borohydride in 10-30 ml of deionized water, stirring for 0.5-2 h to form a sodium borohydride solution with a concentration of 12-18 g / L, to obtain a second solution; S3, taking 2-10 mL of the second solution and adding it dropwise to the first solution at a rate of 1-4 drops / second, and then stirring at room temperature for 10-16 hours; S4, centrifuging the mixed solution of step S3, washing the precipitate with deionized water and ethanol for multiple times, and then vacuum drying at 40-80° C. for 4-12 h to obtain an α-FeOOH sample; S5, adding 80-120 mg of α-FeOOH into a reaction vessel, and adding 15-35 ml of toluene thereto, and performing ultrasound for 15-60 min to ensure that the mixture is evenly dispersed; S6, using an acid regulator to adjust the pH of the mixed solution of step S5 to between 2-5, then heating to 70-100° C., slowly dripping 2-6 mL of APTES, and continuously stirring for 6-12 h. The entire reaction is carried out under the protection of an inert gas; S7. Centrifuge the mixed solution of step S6, wash the precipitate with acetone and ethanol for multiple times, and then vacuum dry it at 40-80° C. for 4-12 hours to obtain an α-FeOOH-NH2 sample.
[0006] Furthermore, in step S1, the iron precursor is selected from ferric sulfate, ferric chloride, and ferric nitrate.
[0007] Furthermore, the reaction container of steps S1 and S5 is a three-necked flask or a four-necked flask.
[0008] Furthermore, the acidic regulator for adjusting the pH in step S1 should be 0.1-0.2M sulfuric acid, nitric acid or hydrochloric acid, and the alkaline regulator should be 0.1-0.2M sodium hydroxide, sodium bicarbonate or potassium hydroxide.
[0009] Furthermore, the acid regulator in step S6 is glacial acetic acid.
[0010] Furthermore, the inert gas in steps S1 and S6 is nitrogen or argon.
[0011] Compared with the prior art, this solution has the following beneficial effects: 1. This scheme weighs hexadecyltrimethylammonium bromide and ferrous sulfate heptahydrate in a certain proportion and adds them to a three-necked flask containing 50 ml of deionized water, adjusts the pH value of the solution to 3, and then stirs under the protection of argon to ensure that the reactants are evenly mixed. At the same time, prepare sodium borohydride (NaBH4) solution, take 2 mL of sodium borohydride and drop it into the above solution, and stir it at room temperature for 14 h to react. After the reaction is completed, use a centrifuge to obtain the precipitate, and wash the precipitate with deionized water and anhydrous ethanol for several times, and finally dry it at 60 ° C in a vacuum environment for 8 hours to obtain α-FeOOH. Weigh 100 mg of α-FeOOH and ultrasonically disperse it in 15 mL of toluene (C7H8). And use glacial acetic acid (C2H4O2) to adjust the pH value of the solution to between 3 and 4, then slowly add 4 mL of 3-aminopropyltriethoxysilane (APTES) at 85 ° C, and continue to stir for 9 h under argon. Afterwards, the solution after the reaction was centrifuged to efficiently separate the surface amino-modified α-FeOOH from the reaction system, and after multiple washings with ethanol and acetone, α-FeOOH-NH2 was finally obtained by drying at 60 °C under vacuum conditions for 12 h. α-FeOOH-NH2 photocatalyst has the characteristics of high specific surface area, excellent selectivity, good hydrophilicity and recyclability; by changing the amount of APTES added to change the degree of amino functionalization, it has broad application prospects in radioactive uranium extraction technology.
[0012] 2. This scheme has the advantages of simple preparation method, low cost and easy control of reaction conditions. The prepared α-FeOOH-NH2 has the characteristics of high specific surface area, excellent selectivity, good hydrophilicity and recyclability. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is the XRD pattern of α-FeOOH prepared in Example 1-4; Figure 2 are (a) transmission electron microscopy (TEM) and (b) high resolution electron microscopy (HRTEM) images of α-FeOOH prepared in Examples 1-4; Figure 3 is the infrared (FT-IR) spectra of α-FeOOH, α-FeOOH-NH2 and α-FeOOH-NH2 prepared in Example 3 after adsorption of uranium; Figure 4 The uranium adsorption performance of α-FeOOH and α-FeOOH-NH2 prepared in Example 3. DETAILED DESCRIPTION
[0014] The present invention is further described in detail below through specific embodiments: Example
[0015] 182 mg of CTAB and 41.7 mg of ferrous sulfate heptahydrate (FeSO4·7H2O) were weighed respectively and added to a three-necked flask containing 60 ml of deionized water. The pH value of the solution was adjusted to 5 by 0.2 mol / L hydrochloric acid and potassium hydroxide, and then stirred under the protection of argon to ensure that the reactants were evenly mixed to form the first solution. At the same time, 151 mg of NaBH4 was weighed and dissolved in 10 mL of deionized water to form the second solution. Subsequently, the treated first solution was transferred to a beaker, and 2 mL of the second solution was added dropwise, and stirred at room temperature for 14 h to react. After the reaction was completed, a precipitate was obtained using a centrifuge, and the precipitate was washed several times with deionized water and anhydrous ethanol, and finally dried at 60 °C in a vacuum environment for 8 hours to obtain α-FeOOH.
[0016] 100 mg of α-FeOOH was ultrasonically dispersed in 25 mL of C7H8 for 30 min to ensure that the mixture was evenly dispersed. Then, the pH value of the solution was adjusted to 5 using glacial acetic acid, and the mixture was transferred to a 50 mL four-necked flask. At 100 °C, 6 mL of APTES was slowly added dropwise and stirred for 12 h under argon. After that, the solution was centrifuged for 30 min at a speed of 8000 r / min to efficiently separate the surface amino-modified α-FeOOH from the reaction system. After multiple washings with ethanol and acetone, α-FeOOH-NH2 was finally obtained by drying under vacuum conditions at 80 °C for 4 h.
[0017] The adsorption performance evaluation method of iron oxyhydroxide for radioactive uranium is as follows: 5 mg of the adsorbent is dispersed in 20 mL of a solution containing 100 ppm uranium, and the adsorption experiment is carried out on a shaker at 25 °C for 4 h. 1.5 to 3.5 ml of the solution is taken at regular intervals, and the adsorbent is filtered out through a filter. The uranium ion concentration is determined by an inductively coupled plasma spectrometer (ICP), and the adsorption capacity of the adsorbent for uranium is calculated according to the adsorption capacity formula. Figure 1 The X-ray diffraction spectrum of α-FeOOH is shown. According to the spectrum, the prepared α-FeOOH has good crystallinity, and the XRD diffraction peak can be well matched with α-FeOOH (PDF#No.77-0247). Figure 2 The transmission image (TEM) and high-resolution image (HRTEM) of α-FeOOH are shown in Figure 2(a). The transmission image shows that the prepared α-FeOOH is a two-dimensional nanosheet material. Figure 2(b) It can be seen that in the high-resolution transmission electron microscopy (HRTEM) image, the lattice fringes with a spacing of 0.256 nm correspond to the (100) crystal plane of α-FeOOH, which corresponds to the highest (100) crystal plane of α-FeOOH in the XDR spectrum. Example
[0018] Weigh 182 mg of CTAB and 23.9 mg of ferric chloride (FeCl3) respectively and add them to a three-necked flask filled with 30 ml of deionized water. Adjust the pH value of the solution to 3 with 0.1 mol / L sulfuric acid and sodium bicarbonate, then stir under the protection of nitrogen to ensure that the reactants are evenly mixed to form the first solution. At the same time, weigh 300 mg of NaBH4 and dissolve it in 20 mL of deionized water to form the second solution. Subsequently, transfer the treated first solution to a beaker, add 5 mL of the second solution dropwise, and stir at room temperature for 10 h to react. After the reaction is completed, use a centrifuge to obtain a precipitate, and wash the precipitate several times with deionized water and anhydrous ethanol, and finally dry it under a vacuum environment at 40 ° C for 12 hours to obtain α-FeOOH.
[0019] 80 mg of α-FeOOH was ultrasonically dispersed in 15 mL of C7H8 for 15 min to ensure that the mixture was evenly dispersed. Then, the pH value of the solution was adjusted to 2.5 with glacial acetic acid, and the mixture was transferred to a 50 mL three-necked flask. At 70 °C, 3 mL of APTES was slowly added dropwise and stirred for 6 h under nitrogen. After that, the solution was centrifuged for 30 min at a speed of 8000 r / min to efficiently separate the surface amino-modified α-FeOOH from the reaction system. After multiple washings with ethanol and acetone, α-FeOOH-NH2 was finally obtained by drying under vacuum conditions at 40 °C for 12 h.
[0020] The adsorption performance evaluation method of iron oxyhydroxide for radioactive uranium is as follows: 5 mg of the adsorbent is dispersed in 20 mL of a solution containing 100 ppm uranium, and the adsorption experiment is carried out on a shaker at 25 °C for 4 h. 1.5 to 3.5 ml of the solution is taken at regular intervals, and the adsorbent is filtered out through a filter. The uranium ion concentration is determined by an inductively coupled plasma spectrometer (ICP), and the adsorption capacity of the adsorbent for uranium is calculated according to the adsorption capacity formula. Figure 1 The X-ray diffraction spectrum of α-FeOOH is shown. According to the spectrum, the prepared α-FeOOH has good crystallinity, and the XRD diffraction peak can be well matched with α-FeOOH (PDF#No.77-0247). Figure 2The transmission image (TEM) and high-resolution image (HRTEM) of α-FeOOH are shown in Figure 2(a). The transmission image shows that the prepared α-FeOOH is a two-dimensional nanosheet material. Figure 2 (b) It can be seen that in the high-resolution transmission electron microscopy (HRTEM) image, the lattice fringes with a spacing of 0.256 nm correspond to the (100) crystal plane of α-FeOOH, which corresponds to the highest (100) crystal plane of α-FeOOH in the XDR spectrum. Example
[0021] 182 mg of CTAB and 41.7 mg of ferrous sulfate heptahydrate (FeSO4·7H2O) were weighed respectively and added to a three-necked flask containing 50 ml of deionized water. The pH value of the solution was adjusted to 3 by 0.1 mol of sulfuric acid and sodium hydroxide, and then stirred under the protection of argon to ensure that the reactants were evenly mixed to form the first solution. At the same time, 151 mg of NaBH4 was weighed and dissolved in 10 mL of deionized water to form the second solution. Subsequently, the treated first solution was transferred to a beaker, and 2 mL of the second solution was added dropwise, and stirred at room temperature for 14 h to react. After the reaction was completed, a precipitate was obtained using a centrifuge, and the precipitate was washed several times with deionized water and anhydrous ethanol, and finally dried at 60 ° C in a vacuum environment for 8 hours to obtain α-FeOOH.
[0022] 100 mg of α-FeOOH was ultrasonically dispersed in 15 mL of C7H8 for 30 min to ensure that the mixture was evenly dispersed. Then, the pH value of the solution was adjusted to between 3 and 4 using glacial acetic acid, and the mixture was transferred to a 50 mL three-necked flask. At 85 °C, 2 mL of APTES was slowly added dropwise and stirred for 9 h under argon. After that, the solution was centrifuged for 30 min at a speed of 8000 r / min to efficiently separate the surface amino-modified α-FeOOH from the reaction system. After multiple washings with ethanol and acetone, α-FeOOH-NH2 was finally obtained by drying under vacuum conditions at 60 °C for 12 h.
[0023] The adsorption performance evaluation method of iron oxyhydroxide for radioactive uranium is as follows: 5 mg of the adsorbent is dispersed in 20 mL of a solution containing 100 ppm uranium, and the adsorption experiment is carried out on a shaker at 25 °C for 4 h. 1.5 to 3.5 ml of the solution is taken at regular intervals, and the adsorbent is filtered out through a filter. The uranium ion concentration is determined by an inductively coupled plasma spectrometer (ICP), and the adsorption capacity of the adsorbent for uranium is calculated according to the adsorption capacity formula. Figure 1The X-ray diffraction spectrum of α-FeOOH is shown. According to the spectrum, the prepared α-FeOOH has good crystallinity, and the XRD diffraction peak can be well matched with α-FeOOH (PDF#No.77-0247). Figure 2 The transmission image (TEM) and high-resolution image (HRTEM) of α-FeOOH are shown in Figure 2(a). The transmission image shows that the prepared α-FeOOH is a two-dimensional nanosheet material. Figure 2 (b) It can be seen that in the high-resolution transmission electron microscopy (HRTEM) image, the lattice fringes with a spacing of 0.256 nm correspond to the (100) crystal plane of α-FeOOH, which corresponds to the highest (100) crystal plane of α-FeOOH in the XDR spectrum. Figure 3 The FT-IR spectra of α-FeOOH, α-FeOOH-NH2 and α-FeOOH-NH2 after adsorption of uranium are shown. By comparing the FT-IR spectrum of α-FeOOH-NH2 with the FT-IR spectrum of α-FeOOH nanosheets, it can be seen that the FT-IR spectrum of α-FeOOH-NH2 at 1626 cm -1 The peak at 1271 cm is the stretching absorption vibration peak of -NH2, indicating that -NH2 has been successfully modified on the surface of α-FeOOH nanosheets. Comparing the FT-IR spectra of α-FeOOH-NH2 nanosheets before and after uranium adsorption, we found that -1 The stretching vibration peak of -UO2 was formed, indicating that the α-FeOOH-NH2 nanosheets successfully adsorbed uranium. Figure 4 The results show that the adsorption performance of uranium by α-FeOOH at pH 8.0 and α-FeOOH-NH2 at pH 7.0 changes with time. Their adsorption capacity for uranium increases sharply in the first 60 min and 2 min, respectively, and then reaches saturation and maintains at a high adsorption level. Example
[0024] 182 mg of CTAB and 35.6 mg of ferric nitrate (Fe(NO3)3) were weighed respectively and added to a three-necked flask containing 40 ml of deionized water. The pH value of the solution was adjusted to 4 by 0.15 mol / L nitric acid and potassium hydroxide, and then stirred under the protection of nitrogen to ensure that the reactants were evenly mixed to form the first solution. At the same time, 540 mg of NaBH4 was weighed and dissolved in 30 mL of deionized water to form the second solution. Subsequently, the treated first solution was transferred to a beaker, and 10 mL of the second solution was added dropwise, and stirred at room temperature for 16 h to react. After the reaction was completed, a precipitate was obtained using a centrifuge, and the precipitate was washed several times with deionized water and anhydrous ethanol, and finally dried under a vacuum environment at 80 °C for 4 hours to obtain α-FeOOH.
[0025] 120 mg of α-FeOOH was ultrasonically dispersed in 35 mL of C7H8 for 60 min to ensure that the mixture was evenly dispersed. Then, the pH value of the solution was adjusted to 4 with glacial acetic acid, and the mixture was transferred to a 50 mL three-necked flask. At 85 °C, 4 mL of APTES was slowly added dropwise and stirred for 9 h under argon. After that, the solution was centrifuged for 30 min at a speed of 8000 r / min to efficiently separate the surface amino-modified α-FeOOH from the reaction system. After multiple washings with ethanol and acetone, α-FeOOH-NH2 was finally obtained by drying under vacuum conditions at 60 °C for 8 h.
[0026] The adsorption performance evaluation method of iron oxyhydroxide for radioactive uranium is as follows: 5 mg of the adsorbent is dispersed in 20 mL of a solution containing 100 ppm uranium, and the adsorption experiment is carried out on a shaker at 25 °C for 4 h. 1.5 to 3.5 ml of the solution is taken at regular intervals, and the adsorbent is filtered out through a filter. The uranium ion concentration is determined by an inductively coupled plasma spectrometer (ICP), and the adsorption capacity of the adsorbent for uranium is calculated according to the adsorption capacity formula. Figure 1 The X-ray diffraction spectrum of α-FeOOH is shown. According to the spectrum, the prepared α-FeOOH has good crystallinity, and the XRD diffraction peak can be well matched with α-FeOOH (PDF#No.77-0247). Figure 2 The transmission image (TEM) and high-resolution image (HRTEM) of α-FeOOH are shown in Figure 2(a). The transmission image shows that the prepared α-FeOOH is a two-dimensional nanosheet material. Figure 2 (b) It can be seen that in the high-resolution transmission electron microscopy (HRTEM) image, the lattice fringes with a spacing of 0.256 nm correspond to the (100) crystal plane of α-FeOOH, which corresponds to the highest (100) crystal plane of α-FeOOH in the XDR spectrum.
[0027] The above are only embodiments of the present invention, and the common knowledge such as the known specific structures and / or characteristics in the scheme are not described in detail here. It should be pointed out that for those skilled in the art, several deformations and improvements can be made without departing from the structure of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing amino-functionalized FeOOH nanosheets for treating uranium-containing wastewater, characterized in that: The steps include: S1, adding CTAB and iron precursor into a reaction container, and adding 30-60 mL of deionized water thereto, then adjusting the pH of the solution to acidic, and then stirring for 30-60 minutes under the protection of an inert gas to obtain a first solution; S2, dissolving a certain amount of sodium borohydride in 10-30 ml of deionized water, stirring for 0.5-2 h to form a sodium borohydride solution with a concentration of 12-18 g / L, to obtain a second solution; S3, taking 2-10 mL of the second solution and adding it dropwise to the first solution at a rate of 1-4 drops / second, and then stirring at room temperature for 10-16 hours; S4, centrifuging the mixed solution of step S3, washing the precipitate with deionized water and ethanol for multiple times, and then vacuum drying at 40-80° C. for 4-12 h to obtain an α-FeOOH sample; S5, adding 80-120 mg of α-FeOOH into a reaction vessel, and adding 15-35 ml of toluene thereto, and performing ultrasound for 15-60 min to ensure that the mixture is evenly dispersed; S6, using an acid regulator to adjust the pH of the mixed solution of step S5 to between 2-5, then heating to 70-100° C., slowly dripping 2-6 mL of APTES, and continuously stirring for 6-12 h. The entire reaction is carried out under the protection of an inert gas; S7. Centrifuge the mixed solution of step S6, wash the precipitate with acetone and ethanol for multiple times, and then vacuum dry it at 40-80° C. for 4-12 hours to obtain an α-FeOOH-NH2 sample.
2. The method for preparing amino-functionalized FeOOH nanosheets for treating uranium-containing wastewater according to claim 1, characterized in that: In step S1, the iron precursor is selected from ferric sulfate, ferric chloride, and ferric nitrate.
3. The method for preparing amino-functionalized FeOOH nanosheets for treating uranium-containing wastewater according to claim 2, characterized in that: The reaction container of steps S1 and S5 is a three-necked flask or a four-necked flask.
4. The method for preparing amino-functionalized FeOOH nanosheets for treating uranium-containing wastewater according to claim 1, characterized in that: The acidic regulator for adjusting the pH in step S1 should be 0.1-0.2M sulfuric acid, nitric acid or hydrochloric acid, and the alkaline regulator should be 0.1-0.2M sodium hydroxide, sodium bicarbonate or potassium hydroxide.
5. The method for preparing amino-functionalized FeOOH nanosheets for treating uranium-containing wastewater according to claim 1, characterized in that: The acid regulator in step S6 is glacial acetic acid.
6. The method for preparing amino-functionalized FeOOH nanosheets for treating uranium-containing wastewater according to claim 1, characterized in that: The inert gas in steps S1 and S6 is nitrogen or argon.
Citation Information
Patent Citations
Soil remediation agent prepared by using rice straw biomass charcoal as raw material and production method of soil remediation agent
CN110699086A
Preparation and application of biomass-based composite hydrogel for radionuclide separation
CN117106203A
FeOOH / ZCS nanocomposite photocatalyst as well as preparation method and application thereof
CN118477661A
Cesium adsorbent, cesium adsorbent producing method, and environmental treatment method using cesium adsorbent
JP2015064339A
Low-Dimensional Structures of Organic and / or Inorganic Substances and Use Thereof
US20160074325A1
Cited By
Functionalized silica gel adsorption material as well as preparation method and application thereof
CN120022853A
